2009
DOI: 10.1007/s00787-009-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

What have birth cohort studies asked about genetic, pre- and perinatal exposures and child and adolescent onset mental health outcomes? A systematic review

Abstract: Background: Increased understanding of early neurobehavioural development is needed to prevent, identify and treat childhood psychopathology most effectively at the earliest possible stage. Prospective birth cohorts can elucidate the association of genes, environment and their interactions with neurobehavioural development. Methods:We conducted a systematic review of the birth cohort literature. On the basis of internet searches and 6,248 peer-reviewed references, 105 longitudinal epidemiological studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 85 publications
0
51
1
Order By: Relevance
“…However, existing birth cohort studies provide us only with limited information regarding the full range of factors which may contribute to the development of mental illnesses (Thompson et al, 2010). Through continuous follow-up of the Taiwan Birth Cohort Study and future nestedcontrolled studies, we hope to continually investigate the association between parents and children, and provide ongoing information regarding the predisposing and maintaining factors which predict the long-term outcome of parental mental health and children's development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, existing birth cohort studies provide us only with limited information regarding the full range of factors which may contribute to the development of mental illnesses (Thompson et al, 2010). Through continuous follow-up of the Taiwan Birth Cohort Study and future nestedcontrolled studies, we hope to continually investigate the association between parents and children, and provide ongoing information regarding the predisposing and maintaining factors which predict the long-term outcome of parental mental health and children's development.…”
Section: Resultsmentioning
confidence: 99%
“…As stated earlier, retrospective studies have the possibility of recall bias, but cohort studies or even birth cohort studies can provide us with a longitudinal understanding of how conditions develop overtime and how exposures in childhood can influence outcomes later in life (Thompson et al, 2010). For instance, the British cohort study, which started in 1970, is one of the longest-standing birth cohort studies with the largest existing sample (Thompson et al, 2010) showing that parental style affects children well into adulthood (Huppert et al, 2010).…”
Section: Prospective Cohort Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies with non-referred samples are more informative of the natural history and distribution of the disorders in the population [5], clinicians working with children and adolescents are also very interested in knowing the rate of child mental disorders in referred samples that resembles more adequately the environment where they work. In LMIC, there is a clear lack of specialized centers for providing care to children suffering from child psychopathology.…”
mentioning
confidence: 99%
“…Whilst we are starting to see psychopharmacological studies in adolescence [1] some readers may be surprised to know that many of the more recently licensed modified release stimulant preparations used in the treatment of ADHD that have been trialled in children and adults are only now being formally trialled in adolescents and few studies have investigated the impact of autism during the teenage years. On the positive side many of the large prospective birth cohort studies have now reported data on adolescent outcomes [11] and specific studies looking at the developmental correlates of adolescence mental health problems have been completed [7].…”
mentioning
confidence: 99%